Efeito antioxidante de extrato de pimenta em óleo de soja sob diferentes condições de estocagem - Pereira, Danusa Cassiano [UNESP] (2013)
This study aimed to evaluate the antioxidant capacity of extracts from red peppers of the genus Capsicum in nature and measure the oxidative stability of soybean oil added of pepper extract, as well as evaluating the resistance of tocopherols naturally present in soybean oil during the accelerated storage tests in stove and at room temperature. In the lyophilized hydroalcoholic extracts of Malagueta, Cumari, Bode, and Dedo-de-moça, the antioxidant activity, by means of antioxidant systems DPPH· (2,2-diphenyl-1-picrylhydrazyl), β-carotene/linoleic acid, FRAP (Ferric Reducing Antioxidant Power), and ABTS·+ (radical 2,2-azinobis-3-ethylbenzothiazoline-6- sulfonic acid), and also the levels of phenolics, total carotenoids, and ascorbic acid were evaluated. Treatments: Control (soybean oil-free antioxidants), TBHQ100 (soybean oil + 100 mg/ kg TBHQ), TBHQ200 (soybean oil + 200 mg/kg TBHQ), BHA100 (soybean oil + 100 mg/kg BHA), BHA200 (soybean oil + 200 mg/kg BHA), Extract100 (soybean oil + 100 mg/kg of total phenolic compounds of Malagueta), and Extract200 (soybean oil + 200 mg/kg of total phenolic compounds of Malagueta) were subjected to the accelerated storage test (60°C/20 days) and to the test at room temperature (28°C/9 months). The treatments were analyzed by measuring the peroxide value, conjugated dienes, oxidative stability index, levels of tocopherols, and mass gain (60ºC/30 days). The results of analytical determinations were subjected to analysis of variance and differences between means were tested at 5% probability by Tukey test. The peppers are good sources of ascorbic acid, carotenoids, and phenolic compounds. These compounds provide the peppers with antioxidant properties, even if they are subjected to oxidative stress conditions. Chilli pepper extracts added to soybean oil as natural antioxidants were capable of reducing the changes suffered by soybean oil during the storage process, thus being able to be natural ...